2021
DOI: 10.3390/app11052048
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Differences in Squamous Precancerous and Cancerous Lesions of the Oral Cavity and the Larynx: Preliminary Data

Abstract: The aim of this study is to assess immune cell populations in squamous precancerous (preinvasive) and cancerous lesions of the oral cavity and larynx. Qualitative and quantitative immunohistochemical analyses were performed to determine the expressions of CD4, CD8, CD15, CD57 and CD68. The expressions of programmed death-ligand 1 (PD-L1), p16 and Ki67 were also assessed. Squamous cell lesions from forty-one patients were included in the study. Sixteen samples were categorized as precancerous (preinvasive) lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Gopi et al analyzed the MRI findings of 9 palatal tumors and found that MRI had significant advantages in assessing structures surrounding malignant tumor infiltration [ 10 ]. Aló et al summarized the typical CT and MRI imaging findings of different histological types of palatal tumors and tumor-like lesions and found that conventional MRI signs can help narrow the range of differential diagnosis [ 11 ]. Cesare et al studied the apparent diffusion coefficient (ADC) value of 32 salivary gland tumors (17 benign and 15 malignant) examined by preoperative diffusion-weighted imaging (DWI), they found that the ADC value could not reliably distinguish benign and malignant salivary gland tumors, and they speculated that the possible reason was that some salivary gland malignancies such as acinar cell carcinoma contained rich extracellular matrix, which led to the increase of the corresponding ADC value [ 12 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gopi et al analyzed the MRI findings of 9 palatal tumors and found that MRI had significant advantages in assessing structures surrounding malignant tumor infiltration [ 10 ]. Aló et al summarized the typical CT and MRI imaging findings of different histological types of palatal tumors and tumor-like lesions and found that conventional MRI signs can help narrow the range of differential diagnosis [ 11 ]. Cesare et al studied the apparent diffusion coefficient (ADC) value of 32 salivary gland tumors (17 benign and 15 malignant) examined by preoperative diffusion-weighted imaging (DWI), they found that the ADC value could not reliably distinguish benign and malignant salivary gland tumors, and they speculated that the possible reason was that some salivary gland malignancies such as acinar cell carcinoma contained rich extracellular matrix, which led to the increase of the corresponding ADC value [ 12 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The microspheres were activated by epichlorohydrin and cross-linked with EGFR antibodies to prepare immune composite microspheres. After the EGFR antibody modified on the surface of the composite microspheres spontaneously binds with EGFR in thyroid cancer and breast cancer cells, EGFR is highly expressed in cancer cells, making the microspheres located at the cancerous site [ 7 ]. Using sodium alginate as carrier material, Konkoová prepared epirubicin-loaded nanodrug carriers with anti-VEGFR2 monoclonal antibodies by polyelectrolyte method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is a vital and important point in checking and screening all premalignant lesions as the possibility and risk of malignant changes is high, and this is agreed with other study obtained by. Aló, P. L. et al 2021 that documented PDL1 expression in premalignant lesions was less frequent as malignant lesion (12).…”
Section: Pdl1 Expression In Laryngeal Carcinomamentioning
confidence: 97%